Pengaruh Corporate Social Responsibility Proporsi Dewan Komisaris Independen Dan Frekuensi Rapat Komite Audit Terhadap Agresivitas Pajak - Denny Novi Satria; Vonni Cristin (LPPM Universitas Dharma Andalas, 2022)
Tax avoidance is an effort by taxpayers to take advantage of the opportunities that exist in the tax law so that taxpayers can pay lower taxes. If tax evasion activities are carried out in accordance with tax laws, then these activities are legal and acceptable activities. This study aims to determine and analyze how much influence Tax Pressure (X1), Independent Commissioner (X2), has on Tax Avoidance (Y) in Construction, Property and Real Estate companies on the Indonesia Stock Exchange. The method used in this study is quantitative using secondary data in the form of annual financial statements of construction, property and real estate companies in the 2016-2020 period. The analysis technique used is panel data regression. Based on the results of research and analysis of Financial Pressure (X1) which is proxied by ROA has a significant effect on Tax Avoidance in Construction, Property and Real Estate companies on the Indonesia Stock Exchange, and Independent Commissioners have no effect on Tax Avoidance in Construction, Property and Real Estate companies on the Stock Exchange. Indonesian Effect.